China’s international ship registration system against the backdrop of construction of the Hainan Free Trade Port - Shi, Yuanhong; Shi, Yiji; Zhou, Hui (Frontiers in Marine Science, 2025)
The international ship registration system is an important component of shipping policy. A review of its historical development in China reveals that its implementation has yet to achieve the intended outcomes. The construction of the Hainan Free Trade Port presents a valuable opportunity to advance the development of this system. Based on the Theory of Change Model, this study assesses the current state of China’s international ship registration system within the context of the Hainan Free Trade Port. We also employ research methods such as SWOT analysis and comparative analysis to objectively assess the implementation of this innovative policy from both macro and micro perspectives, as well as from qualitative and quantitative angles. Our analysis identifies a range of persistent challenges, including imperfect supporting policies and insufficient regulatory oversight. In response, we propose a series of reform measures spanning legislative, judicial, and law enforcement dimensions. These include restructuring the taxation system for shipping enterprises, enhancing the regulatory framework for ship registration, and developing a robust system of ancillary services. Collectively, these reforms are essential for comprehensively strengthening the maritime soft power of China’s shipping industry.